Cholera Epidemics of the Past Offer New Insights Into an Old Enemy. (20th November 2017) - Phelps, Matthew; Perner, Mads Linnet; Pitzer, Virginia E; Andreasen, Viggo; Jensen, Peter K M; Simonsen, Lone
Abstract : We investigate cholera transmission using data from historical cholera epidemics. The results suggest short-cycle (household/institution level) transmission was important in early secondary transmission. This study of historical outbreaks can inform investigations in current cholera epidemic settings. Abstract: Background: Although cholera is considered the quintessential long-cycle waterborne disease, studies have emphasized the existence of short-cycle (food, household) transmission. We investigated singular Danish cholera epidemics (in 1853) to elucidate epidemiological parameters and modes of spread. Methods: Using time series data from cities with different water systems, we estimated the intrinsic transmissibility (R0 ). Accessing cause-specific mortality data, we studied clinical severity and age-specific impact. From physicians' narratives we established transmission chains and estimated serial intervals. Results: Epidemics were seeded by travelers from cholera-affected cities; initial transmission chains involving household members and caretakers ensued. Cholera killed 3.4%–8.9% of the populations, with highest mortality among seniors (16%) and lowest in children (2.7%). Transmissibility (R0 ) was 1.7–2.6 and the serial interval was estimated at 3.7 days (95% confidence interval, 2.9–4.7 days). The case fatality ratio (CFR) was high (54%–68%); using R0 we computed an adjusted CFR of 4%–5%. Conclusions: Short-cycle transmission was likely critical to early secondary transmission in historic Danish towns. The outbreaks resembled the contemporary Haiti outbreak with respect to transmissibility, age patterns, and CFR, suggesting a role for broader hygiene/sanitation interventions to control contemporary outbreaks.